Chance-Constrained Programming with Joint Constraints - Jagannathan, R. (Operations Research, 1974)
Miller and Wagner have shown that a deterministic equivalent of a joint chance-constrained programming model with independent random right-hand-side elements is a concave programming problem. This paper obtains similar equivalents for chance-constrained programming models with coefficient matrices whose elements are normally distributed and with dependent random right-hand-side elements.